Soil influences on plant growth, floral density and nectar yield in three cultivars of mānuka (Leptospermum scoparium). Issue 2 (3rd April 2017) - Nickless, Elizabeth M.; Anderson, Christopher W. N.; Hamilton, Georgie; Stephens, Jonathan M.; Wargent, Jason
ABSTRACT: Honey derived from the nectar of Leptospermum scoparium J.R. et G. Forst. Myrtaceae (mānuka) is a high-value product and there is considerable potential for economic growth in honey-growing regions of New Zealand through increased nectar yield from mānuka plantations. Leptospermum scoparium exhibits a significant amount of phenotypic plasticity throughout regions in New Zealand where it has established, although the influences on this plasticity are unknown. When assessing L. scoparium as a nectar source for honey in marginal land areas, the possible effect of soil on nectar chemistry and yield should be considered. We investigated whether phenological patterns of flowering, plant growth, nectar composition and nectar yield were influenced by soil composition. Three different cultivars of L. scoparium were grown on 10 different soils in glasshouse conditions. The soils chosen were representative of the range of New Zealand soils where mānuka is being considered as a commercial crop for the honey industry. ANOVA and general linear models revealed no significant effect of soils on nectar composition or production; however, significant but complex interactions between cultivars and soils influenced plant growth and flowering ( P ≤ 0.05). Accordingly, the overall nectar yield was influenced by cultivar and soil interaction. Measured attributes of the soil such as cation exchange capacity, sulphate, iron, manganese, calcium and chloride were shown to influence the plant parameters assessed. Results allowed modelling of nectar potential against each soil type and established a mānuka soil index to determine the most appropriate soil for each cultivar. The results indicated that potential nectar yield increases will be dependent on cultivars being deployed according to the nature of the soil present. Furthermore, the mānuka cultivars displayed significantly greater growth in response to increased nutrients and some cultivars increased floral density, suggesting potential to improve nectar yield by greater plant growth using targeted fertilisation.